The Magnetic/Electrical Phase Diagram of Cr-Doped Antiperovskite Compounds GaCFe3−xCrx (0≤x≤0.9) - S. Lin; B. S. Wang; P. Tong; D. F. Shao; Y. N. Huang; W. J. Lu; B. C. Zhao; W. H. Song; Y. P. Sun (Advances in Condensed Matter Physics)
We report the effect of Cr doping on the structural, magnetic, and electrical transport properties in Cr-doped antiperovskite compounds GaCFe3−xCrx (0≤x≤0.9). With increasing the Cr content x, the lattice constant increases while both the Curie temperature and the saturated magnetization decrease gradually. The electrical resistivity shows different behaviors as a function of x. For x≤0.6, there exists a semiconductor-like behavior below a certain temperature which decreases with increasing x. In contrast, for 0.7≤x≤0.9, the resistivity shows a metallic behavior in the whole temperature measured (2–350 K). In particular, the Fermi-liquid behavior is obtained below 70 K. Finally, based on the magnetic and electrical properties of GaCFe3−xCrx (0≤x≤0.9) a magnetic/electrical phase diagram was plotted.